Ownership Structure on Dividend Policy in The Indonesian Stock Exchange - Vincent; Liliana Ingrit Wijaya; Werner Ria Murhadi (Journal of Entrepreneurship and Business, 2023)
Purpose: This research analyses how ownership structure affects dividend policy. Method: Quantitative with a pool least square (PLS) regression model was used as a research method, and the research sample was drawn from all non-financial sector companies registered in IDX from 2017 to 2021. Independent variables such as family ownership, institutional ownership, and concentration ownership. This research also has a control variable such as return on assets, debt to equity ratio, firm size, firm age, free cash flow, and volatility (business risk). Result: This research found that family ownership, institutional ownership, concentration ownership, return on assets, firm size, age of firm, free cash flow, and volatility (business risk) all have a significant effect on dividend yield, but the debt to equity ratio has no effect.